1980
DOI: 10.1002/ajim.4700010109
|View full text |Cite
|
Sign up to set email alerts
|

Changes in psychological performances of solvent‐poisoned and solvent‐exposed workers

Abstract: The changes in psychological performances associated with long-term exposure to organic solvents and solvent mixtures were studied in a group of 56 male workers diagnosed as having an occupational disease caused by solvents. Their mean duration of exposure was 9.1 +/- SD 8.3 years, and they were exposed mainly to halogenated and aromatic hydrocarbons and to mixtures of paint solvents. The psychological performances of these solvent-exposed patients were compared with those of 98 styrene-exposed workers and a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0
2

Year Published

1980
1980
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(22 citation statements)
references
References 7 publications
1
19
0
2
Order By: Relevance
“…Both clinical and epidemiologic studies, primarily originating from Scandinavia, suggest that painters have an elevated risk of neurological deficits and possibly chronic neuropsychiatric disorders (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, outside Scandinavia, few if any studies have been done to evaluate the risk of chronic neuropsychiatric disease among painters.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both clinical and epidemiologic studies, primarily originating from Scandinavia, suggest that painters have an elevated risk of neurological deficits and possibly chronic neuropsychiatric disorders (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). However, outside Scandinavia, few if any studies have been done to evaluate the risk of chronic neuropsychiatric disease among painters.…”
mentioning
confidence: 99%
“…Moreover, deficits in visual intelligence and memory have been associated with organic solvent exposure (3)(4)(5). These impairments among painters were also found two years after the initial diagnosis (6) or were present when diagnosed five or more years after the termination of the solvent exposure in question (7).…”
mentioning
confidence: 99%
“…Et il s'ensuit que ce sont les travailleurs «en santé» qui restent aux postes les plus exposés. Ce phé-nomène relève ce de qu'on a appelé le «syndrome du travailleur en santé» («healthy worker syndrome») (Gregersen et al, 1984;Lindstrom, 1980). Dans ce cas, l'évaluation des modifications neurocomportementales se fait sur des personnes ayant une meilleure résistance apparente aux agents neurotoxiques.…”
Section: Les Symptômes Générauxunclassified
“…Analysant les résultats de cinq études finlandaises sur les effets neurotoxiques de l'exposition à long terme aux solvants organiques, Lindstrom (1980) fait ressortir l'importante interaction de divers facteurs qui influencent l'état psychologique («psychological end-state») des personnes exposées. H propose un modèle écologique d'interaction dynamique entre l'environnement, pris dans son sens large, et les fonctions physiologiques et psychologiques des personnes exposées: ce qui lui permet de comprendre la complexité de la situation.…”
Section: Le Système Nerveux Subit L'influence D'une Diversité De Factunclassified
“…Several psychological studies have shown that painters and other workers with solvent exposure have disturbed psychological functions and emotional reactions (3,4,6). Patients with solvent intoxication were found to have electroencephalographic abnormalities and also impairment in memory, concentration, and sensory and motor functions (1,10).…”
mentioning
confidence: 99%